Comparison of Perioperative Outcomes of Robot-Assisted vs. Laparoscopic Radical Nephrectomy: A Systematic Review and Meta-Analysis - Li, Jinze; Peng, Lei; Cao, Dehong; Cheng, Bo; Gou, Haocheng; Li, Yunxiang; Wei, Qiang (Frontiers in Oncology, 2020)
Background: The use of robot-assisted radical nephrectomy (RARN) for renal cell carcinoma (RCC) has increased in recent years, but the advantages of RARN over laparoscopic radical nephrectomy (LRN) remain controversial. This study aimed to compare the perioperative outcomes between RARN and LRN. Methods: We systematically searched the Embase, PubMed, Web of Science, and CNKI databases to identify eligible comparative studies. The parameters were perioperative outcomes including operating time (OT), estimated blood loss (EBL), length of stay (LOS), conversion rate, and complications. Stata 15.0 software was used for the meta-analysis. Results: Seven studies with 1,832 patients were included in the analysis. Among them, 532 underwent RARN and 840 underwent LRN for renal cell carcinoma. There were no significant differences in OT (weighted mean difference [WMD], 29.05; 95% confidence interval [CI], –0.31, 58.41; p = 0.05), EBL (WMD, –4.56; 95% CI, –29.79, 20.67; p = 0.72), LOS (WMD, –0.34; 95% CI, –0.68, 0.00; p = 0.05), conversion rate (WMD, 2.67; 95% CI, 0.68, 10.46; p = 0.05), transfusion rate (odds ratio [OR], 1.30; 95% CI, 0.74, 2.27; p = 0.36), intraoperative complications (OR, 1.13; 95% CI, 0.61, 2.12; p = 0.62), and postoperative complications (OR, 1.07; 95% CI, 0.68, 1.67; p = 0.62) between the two groups. Conclusion: RARN was not superior to LRN in patients with RCC in terms of perioperative outcomes. Before establishing conclusive clinical recommendations, high-quality prospective large-scale randomized controlled trials with long-term follow-up are needed.